A new species of Bregmaceros (Gadiformes: Bregmacerotidae) from the eastern Pacific Ocean, with comments on B. atlanticus and B. japonicus - Harold, Antony S.; Baltzegar, D. Andrew (Zootaxa, 2023)
A new species of Bregmaceros is described based on a series of specimens from the eastern Pacific Ocean from near the Hawaiian Islands eastward to the California Current region. The new species bears considerable similarity in body shape and pigmentation to other overall darkly pigmented species with moderately high anal-fin counts (51–59 in B. moseri) and modified prehaemal anal-fin pterygiophores (B. atlanticus and B. japonicus). The form and occurrence of these modified pterygiophores among Bregmaceros species is discussed. The new species is distinguished from B. atlanticus and B. japonicus and other undescribed forms in the historical literature commonly referred to Bregmaceros “mcclellandi” based on its high precaudal (prehaemal) vertebral counts (15 or 16 vs. 13–15, typically 14) and associated elongation of the anterior portion of the body, and dark pigmentation concentrated dorsally on body and on head dorsal to nares anteriorly and operculum posteriorly but little or no pigment on lateral and ventral surfaces of head. The new species uniquely shares with these other species the modified prehaemal anal-fin pterygiophores and a lack of posterior bifurcation of the coelomic space otherwise present in the remaining species in the genus.